De-commemoration removing statues and renaming places - Gensburger, Sarah 1976-; Wüstenberg, Jenny (Berghahn, 2024)
In the wake of recent protests against police violence and racism, calls to dismantle problematic memorials have reverberated around the globe. This is not a new phenomenon, however, nor is it limited to the Western world. De-Commemoration focuses on the concept of de-commemoration as it relates to remembrance. Drawing on research from experts on memory dynamics across various disciplines, this extensive collection seeks to make sense of the current state of de-commemoration as it transforms contemporary societies around the world.
Keywords: Geschichte; Politischer Ikonoklasmus; Gedenkstätte; Kollektives Gedächtnis; Entkolonialisierung; Politisches Symbol; Aufsatzsammlung